The perception and value of performance analysis within elite academy football: A comparison between phases - Dhillon, C. L.; Nicholls, S. B.; Woodward, J. (International Journal of Sports Science & Coaching, 2025)
The originality of study ascertained coaches` engagement and integration of Performance Analysis (PA) practice across the Foundation (FP), Youth Development (YDP), and Professional Development (PDP) phases within elite academy youth football. Sixty-five (65) coaches (experience 5.5 ± 4.0) completed an online survey focusing upon their utilisation and access to analysis tools, recollection and reflective practice, communication and professional relationship, suggested improvements and current value of PA services. Likert scales (Always, Usually, Sometimes, Rarely, No Access) were used to facilitate comparison. Analysis was undertaken using Kruskal-Wallis and Dunn's post hoc tests to identify differences in response provision between academy phases. The engagement and integration of PA practices varied significantly across phases due to time, resources, and buy-in. PA usage progressed from FP to PDP, with greater integration and more sophisticated tools becoming prevalent towards the latter stages of a player's academy journey. Overall satisfaction with PA services was high, but clear improvement areas were highlighted, particularly around Independent Learning Plans (ILP) and the presence of analysts during training sessions across all phases. Despite the introduction of the Elite Player Performance Plan (EPPP), the study's significance highlights insufficient guidance on how PA should be distributed across phases. This has led to a disproportion of PA across phases with the potential benefits for the FP and YDP being under realised.